Goals 2000: Disastrous Unintended Consequences - Seidman, Robert H. (Education Policy Analysis Archives, 1996)
"Goals 2000: Educate America Act" aims to, among other things, increase the high school graduation rate to at least 90% and eliminate the graduation rate gap between minority and non-minority students. However well intentioned, this goal is doomed to failure. Powerful systemic forces converge to stabilize the high school graduation rate at about 75% where it has been since 1965 and where no traditional national policy will be able to advance it very much. Even if education policy could succeed in increasing the rate to 90% or beyond, undesirable consequences of potentially great magnitude, especially for the targeted minority groups, would result.